Executive Committee Minutes 2017-11-16 - Academic Senate:::::::::
Agenda – Approved. Minutes of 11/2/17 – Approved. President Report. Revision: WGS program, major, minor, queer studies minor approved for the Senate consent calendar. Discontinuance: Career Minor in Women's Health approved for the Senate agenda. Offsite Business Degree Completion Program at College of Marin approved for the Senate agenda. Revision: Applied Physics to Astrophysics concentration approved for the Senate consent calendar. Teacher and Non-Teacher access to LMS policy referred to ATISS via APARC. Posthumous Certificate of Recognition for Paulette Quiba approved for the Senate agenda. English Department resolution presented. Senate Agenda approved.